Micro Operation System for Microprocessor Applications - Krejcar, O.; Spicka, I.; Frischer, R. (Elektronika ir Elektrotechnika, 2011)
To implement Real-time applications for embedded systems we often using microprocessor systems. Especially when using single-chip microprocessors, we are limited with size of the operation and program memory. Then it appears to be disadvantage to use conventional RTOS, which occupy unnecessarily amount of memory, and most of their services will remain unused. The first papers part is intended to the description of the general management philosophy of the microprocessor applications. There are set goals that should easy control of the separate tasks should meet. It is shown, that the appropriate strategy is to separate processing of input signals, custom application and output signals into CPU peripherals. To synchronize the processes in embedded applications is sufficient to implement the wait states, the sleeps state, and some synchronization means. Presented system includes subsystems: (a) the cooperative management as many as eight to sixteen tasks for time-independent role and (b) preemptive multitasking for time role management. In this mode are solved objective tasks of numerical control and implementation of PID controllers. The second papers part then show concrete sample applications of digital control, including operator control. The proposed solution will bring simplified design of digital control applications, when the commercially delivered applications are unnecessary robust and solve task like file management etc. Proposed solutions will reduce tasks management the minimum, so that minimizes memory demands of the microprocessor units with providing basic management tasks. Ill. 5, bibl. 9 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.702